Registration of near-isogenic winter wheat germplasm contrasting in Fhb1 for Fusarium head blight resistance - Bernardo, Amy; Bai, Guihua; Yu, Jianbin; Kolb, Fred; Bockus, William W.; Dong, Yanhong (My University, 2014)
The Chinese wheat Ning7840 (Triticum aestivum L.) contains Fhb1, a major quantitative trait locus (QTL) for Fusarium head blight (FHB) resistance, and has been widely used as a resistant parent in breeding programs worldwide, but due to its poor adaptation in the US, its progenies usually exhibit reduced grain yield due to the transfer of undesirable genes from Ning7840. The development of five near-isogenic lines (NILs, ‘Clark’*7/Ning7840) (NIL75, Reg. No. GP--, PI- --; NIL78, Reg. No. GP--, PI---; NIL80, Reg. No. GP--, PI---; NIL90, Reg. No. GP--, PI---, NIL98, Reg. No. GP--, PI---) contrasting in Fhb1 alleles was intended to overcome this potential limitation. Marker-assisted backcrossing was used to develop the NILs. Approximately 2000 BC7F2 plants from the backcross of Ning7840 by Clark (recurrent parent) were screened with two Fhb1-flanking markers (Xgwm533 and Xgwm493), and selected BC7F3 families were evaluated for FHB resistance in greenhouses. Both genotypic and phenotypic data confirm the presence of Fhb1 in the four resistant NILs and absence in the one susceptible NIL. All resistant NILs had significantly higher FHB resistance and lower deoxynivalenol (DON) content than Clark and the susceptible NIL but yield similar to Clark (P = 0.295). Marker-assisted backcross efficiently transferred Fhb1 into US hard winter wheat without transferring undesirable traits from Ning7840, and these Fhb1 NILs should be useful parents for effective use of Fhb1 in US winter wheat.
Citation: Bernardo, Amy, Guihua Bai, Jianbin Yu, Fred Kolb, William Bockus, and Yanhong Dong. “Registration of Near-Isogenic Winter Wheat Germplasm Contrasting in Fhb1 for Fusarium Head Blight Resistance.” Journal of Plant Registrations 8, no. 1 (2014): 106–8. https://doi.org/10.3198/jpr2013.05.0021crgs.
Keywords: Fusarium head blight; Fhb1; Winter wheat; Wheat